Marginal tax rates and tax-favoured pension savings of the self-employed: Evidence from Sweden - Håkan Selin (Center for Economic Studies and ifo Institute (CESifo), 2010)
In recent years, the study of how individuals respond to policies that aim at promoting pension savings has emerged as a vital area of economic research. This paper adds to this literature by estimating the tax price elasticity of contributions to tax-favoured pension savings accounts on a population of self-employed individuals. I exploit a unique total data base over the Swedish population that covers the years 1999 to 2005. Using instrumental variables, I obtain a tax price elasticity estimate of -0.51 and an income elasticity estimate of 0.13, whereas OLS produces estimates that conflict with consumer theory.
Keywords: G23; H24; J33; J26; 330; income taxation; fringe benefits; individual pension savings; self-employment; Selbstständige; Einkommensteuer; Alterssicherung; Steuerbegünstigung; Elastizität; Schweden